Clinical feasibility of dried blood spots: analytics, validation, and applications - Enderle, Yeliz; Foerster, Kathrin; Burhenne, Jürgen (Journal of pharmaceutical and biomedical analysis, 2016)
Dried blood spots (DBS) sampling and their specific advantages are becoming common in analytical and clinical routine. Being first established for metabolic disorder screening in neonates, its use emerged to a broad spectrum of clinical applications. Although DBS are easily generated, the conduction of specific analytical and clinical validation procedures should be obligatory when implementing DBS for clinical purposes, e.g. therapeutic drug monitoring or clinical drug trials. A respective recommendation has already been published by the European Bioanalysis Forum. Since no official guidelines are present, investigators are currently free in DBS procedure development and validation. This review summarizes and discusses published clinical validation procedures in relation to their applications to highlight the clinical feasibility of DBS.